Influencing factors for postpartum depression in women with gestational diabetes mellitus - Tan, Jinfeng; Xiong, Yujing; Wang, Xiaohui; Wei, Shiyao; Luo, Chunqi; Huang, Shaoming; Yang, Yan; Chen, Jinxia; Chen, Jiebing; Xu, Min; Wu, Fengchun (Frontiers in Endocrinology, 2024)
Objective It remains undefined about the association between gestational diabetes mellitus (GDM) and postpartum depression (PPD). Hence, a cross-sectional study was conducted to evaluate the association between GDM and PPD among pregnant women and to investigate the influencing factors for PPD. Methods From June 2021 to June 2022, 205 parturients with GDM and 201 without GDM were included in the study as the GDM group and the control group, respectively. The collected data from the general information questionnaire and Self Rating Depression Scale (SDS) were statistically analyzed based on binomial logistic regression analyses and generalized linear mixed models (GLMMs). Results Age at delivery, gestational age, glycosylated hemoglobin, triglyceride, SDS, and proportions of women who had a history of induced abortion or GDM were significantly different between the GDM group and control group (P<0.05). The incidence of PPD in the GDM group was significantly higher than that in the control group. The neonatal body weight and triglyceride in GDM women with PPD were significantly lower than those in GDM women without PPD (P<0.001). The univariate logistic regression analysis demonstrated that educational age was a protective factor, while glycosylated hemoglobin and GDM were risk factors for PPD. The multiple linear regression analysis revealed that neonatal body weight (OR=-0.904, 95%CI: -1.657 to -0.152, P=0.019) and educational age (OR=-0.166, 95%CI: -0.306 to -0.025, P=0.021) were protective factor, while GDM (OR=1.854, 95%CI: 1.027-2.681, P<0.0001) was a risk factor for PPD. Conclusion GDM may be associated with PPD. Neonatal body weight and educational age were protective factors for PPD, and GDM was a risk factor for PPD. Therefore, more attention should be paid to the mental health status of women with GDM, especially those with lesser educational age and lower neonatal body weight.